Non-State Actors of Protection and the Sliding Scale of Protection for Refugee Women. (9th July 2022) - Querton, Christel
Abstract: The article argues that although the gradual recognition of non-State actors as agents of persecution was hailed as a success in ensuring better protection for refugee women at risk of harm from their community or family, the associated development of non-state actors as agents of protection has had a detrimental impact on the protection of refugee women in Europe and more globally. More specifically, the article identifies various everyday practices of reliance on male family members and undefined social networks as actors of protection. These co-constructing practices are exercised by different entities involved in refugee status determination processes, including governments, national and regional courts, and regional and international asylum agencies. Although the trend has gone largely unnoticed, it has resulted in a sliding scale of protection for refugee women. The article argues that endorsing non-State actors of protection, such as male family members and undefined social networks, amounts to a requirement that women seeking asylum take action to avoid being persecuted by placing themselves under the protection of those private actors. This is contrary to international refugee law doctrine, fails to consider the possibility of new forms of harm and is, in itself, a breach of women's human rights.